PERTANGGUNGJAWABAN MARKETPLACE TERHADAPPHISHING YANG DILAKUKAN MERCHANT KEPADAKONSUMEN - Aldian Satria Putra, (2022)
The rapid development of technology in line with the commercial world is also growing rapidly. Of course, this makes things easier for consumers and businesses alike. However, there are still a few problems that exist in the buying and selling process on the Marketplace between business actors and buyers. Phishing cases in recent times often occur even in Electronic System Operators, as a form of forum in bringing together consumers and sellers. Data from BPKN disclosed in the period January to May 2021 related to Reports or Complaints against the ecommerce sector as many as 524 Complaints with an emphasis on phishing. In handling it with examples of phishing cases in Bukalapak and Tokopedia, the marketplace only stops in deactivating accounts. There is no follow-up action along with good faith to consumers as service users from the marketplace, so it is worth asking whether it is appropriate and what the consumer's efforts are if they experience losses due to this. The method used in this research is normative legal research, by taking a statute approach to examine existing regulations or regulations. The results of the study show that phishing violations do not only occur because of negligence on the part of consumers. Because the marketplace platform providers Bukalapak and Tokopedia should also take part in preventing the occurrence of phishing violations, the Electronic System Operators for the Bukalapak and Tokopedia Marketplace Platforms must also be charged and held accountable for their failure to run an electronic system business with the name in terms of prevention and efforts that consumers can take are: through litigation and non-litigation channels